Jovellanos: the Enlightenment, economics and «public happiness» - Joaquín OCAMPO SUÁREZ-VALDÉS (Cuadernos Dieciochistas)
From mid XVIII Century, an intensification of international circulation of economic ideas made Spain participate in the emergence of Political Economy as a discipline in the service of public felicity. Jovellanos did not fail to contribute to the new science. His life and professional development, as well as the particular circumstances of the period, explain the fact that the reforming emergencies became the priorities in his duties as an economist: economic theory was placed in the service of applied economics. The aim of this paper is to provide a synthetic view of the above mentioned question.